The Influence of Socio-Economic Status and Self-Efficacy on Students' Academic Achievement: The Intervening Role of Learning Interest - Pasha, Rafli; Hermawan, Yoni; Sartika, Sri Hardianti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research primarily examines the influence of socio-economic status and self-efficacy on academic achievement, with learning interest as an intervening variable. The quantitative research method utilized a survey technique conducted with students of SMAN 1 Manonjaya consisted of 462 social class students with a sample of 206 students selected using simple random sampling. The research instrument was a questionnaire with 40 statement items, all scored using a 5-point Likert scale and data analysis employed path analysis. Results indicated that socio-economic status and self-efficacy influences on learning interest, socio-economic status and self-efficacy do not influence academic achievement, learning interest influences on academic achievement, socio-economic status does not influence academic achievement through learning interest, and self-efficacy does not influence academic achievement through learning interest.